Snakebite envenoming in children: A neglected tropical disease in a Costa Rican pediatric tertiary care center - Brenes Chacón, Helena (2019)
Background: Introduced in June 2017 by the World Health Organization (WHO) as a Neglected Tropical Diseases, snakebite envenoming is a global health problem. In Costa Rica, an incidence of 15 per 100,000 inhabitants and a mortality rate of 0·15 per 100,000 inhabitants per year were reported from 2005-2012. Children are also affected and prone to complications. Methods: Retrospective descriptive 14-year study of children with envenomings by Viperidae snakebites managed at the tertiary pediatric hospital in Costa Rica. Findings: 80 patients (pts) were included and classified as having mild (17 pts, 29·3%), moderate (58 pts, 72·5%) or severe (5 pts, 6·2%) envenoming. 52/80 (65%) patients received treatment within the first four hours, three (3·75%) between 5-8 hours, three between 9-12 hours, four (4%) between 13-16 hours, two (2·5%) between 17-20 hours, and seven (8·75%) after 20 hours. Edema was documented in 76/80 (95%), pain in 58 (72·5%), local bleeding in 23 (28·8%), emesis in 10 (12·5%), bullae formation in 8 (10%), and tissue necrosis in three (3·8%) pts. Complications presented according with degree of envenoming, being more common in severe cases: wound infection occurred in 14/58 (24·1%) with moderate envenoming and 5/5 pts with severe envenoming (p <0·0001), bleeding presented in 3/58 (5·2%) with moderate cases, and 2/5 (40%) in pts with severe envenoming (p=0·004); and compartmental syndrome occurred in 3/17 (17·6%) pts with mild envenoming, in 33/58 (56·9%), and 5/5 of moderate and severe envenomed pts, respectively (p=0·0014). Sequelae were documented 25/80 (31%). Interpretation: Early evaluation and prompt antivenom administration are the keystones of treatment. Complications in these pediatric patients occur frequently: compartmental syndrome, wound infection, and bleeding are the most important. Sequelae were higher than in previous reports, leading to the need of long-term evaluations and prompt therapies.